2022
DOI: 10.54986/irjee/2022/oct_dec/13-21
|View full text |Cite
|
Sign up to set email alerts
|

Socio-personal Profile of APMC Women Involved in Post-harvest Activities of Dry Chilli and their Constraints – A Comparative Study

Abstract: A comparative study to know the socio-personal profi le, constraints and health problems of APMC women involved in post-harvest activities of dry chilli was undertaken during 2019-2020 in Byadgi APMC of Karnataka and Guntur APMC of Andhra Pradesh with a sample of 120 women labourers. The results showed that, 63.33 per cent of Byadgi AMPC and 70.00 per cent of Guntur APMC respondents belonged to middle aged (36- 50) category. More than half (53.33 %) of Byadgi APMC and 63.33 per cent of Guntur APMC women labour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
4
1
0
Order By: Relevance
“…Size of Family: The data presented in Table 1 revealed that more than half (60.00 per cent) of the SHGs women had small family size followed by 29.17 and 10.83 per cent had medium and big family size respectively. This result is in line with the result reported by Deshpande et al (2022), Jhansi and Kalal (2022) and Shinde et al (2021). Occupation : Data in Table 1 reveals that the majorities (43.33%) of the respondents were belonged to Agriculture + Labour followed by Homemakers (22.50%) and only 5.00 per cent have government job and business.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Size of Family: The data presented in Table 1 revealed that more than half (60.00 per cent) of the SHGs women had small family size followed by 29.17 and 10.83 per cent had medium and big family size respectively. This result is in line with the result reported by Deshpande et al (2022), Jhansi and Kalal (2022) and Shinde et al (2021). Occupation : Data in Table 1 reveals that the majorities (43.33%) of the respondents were belonged to Agriculture + Labour followed by Homemakers (22.50%) and only 5.00 per cent have government job and business.…”
Section: Resultssupporting
confidence: 93%
“…Social Participation : Table 1 shows that social participation of respondents depicted one organization (67.50%) followed by more than one organization (29.17%) and some of the respondents (3.34%) not involved in any organization. The fi nding was in concurrence with the fi ndings reported by Jhansi and Kalal (2022). Source of information : In source of information, majority respondents falls in KVK scientist (25.00%) group of personal cosmopolite, television (8.34%) in mass contact group and followed other groups.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…4,56,000 (51.00%). Furthermore, a substantial portion exhibited moderate levels of mass media exposure (57.00%), and medium information seeking behavior (58.00%), the results were similar to studies done by Jhansi and Kalal [6] and Shubham et al [7].…”
Section: Characteristics Of the Respondentssupporting
confidence: 87%
“…Sons get the best food in terms of both quality and quantity, whereas daughters' food is insignifi cant (De, 2017). Preparing her in strenuous household chores so that she can adjust to the diffi cult role of wife to mother is prioritized, while the son, who is viewed as the savior of old age and future breadwinner, is sent to school (Jhansi and Kalal, 2022). If a girl does better in school than her brother, the son is given priority in receiving higher education (Pal 2004).…”
mentioning
confidence: 99%